2022
DOI: 10.1097/rlu.0000000000004023
|View full text |Cite
|
Sign up to set email alerts
|

Increased 68Ga-FAPI Activity in Chondrosarcoma of Nasal Cavity

Abstract: Chondrosarcoma is a rare entity tumor, which mainly appears in long bones and pelvic bones, but rarely in nasal cavity. Herein, we report the 68 Ga-FAPI PET/CT findings in a 54-year-old man with chondrosarcoma of nasal cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In one case report, 68 Ga-FAPI-46 helped in the diagnosis of malignant melanoma of the nasal cavity [265]. In another case report, 68 Ga-FAPI-46 was used in the diagnosis of chondrosarcoma of the nasal cavity [266].…”
Section: Role Of Pet/ct In the Management Of Sinonasal Malignancies U...mentioning
confidence: 99%
“…In one case report, 68 Ga-FAPI-46 helped in the diagnosis of malignant melanoma of the nasal cavity [265]. In another case report, 68 Ga-FAPI-46 was used in the diagnosis of chondrosarcoma of the nasal cavity [266].…”
Section: Role Of Pet/ct In the Management Of Sinonasal Malignancies U...mentioning
confidence: 99%
“…It has high tumor uptake and low background uptake in the detection of most type of cancers. [7][8][9] The case of Wu et al demonstrated that 68 Ga-FAPI outperformed 18 F-FDG in imaging myeloid sarcoma. 10 However, our case showed that there was no obvious difference between 68 Ga-DOTA-FAPI-04 and 18 F-FDG in the evaluation of myeloid sarcoma.…”
mentioning
confidence: 99%
“…Previous studies have reported the use of 18 F-FDG PET/CT in staging and response assessment in myeloid sarcoma.5,6 68 Ga-DOTA-FAPI-04 is a novel tumor tracer based on fibroblast-activation protein. It has high tumor uptake and low background uptake in the detection of most type of cancers [7][8][9]. The case of Wu et al demonstrated that…”
mentioning
confidence: 99%
See 1 more Smart Citation